Implementasi Kurikulum Merdeka Sebagai Upaya Meminimalisir Krisis Sistem Pendidikan Indonesia - Iskandar, Sofyan; Rosmana, Primanita Sholihah; Nabilah, Khairun; Pebriyanti, Paola; Prayoga, Rizki; Faqih, Abdillah (JURNAL SINEKTIK, 2024)
In life there are always changes, including the world of education. The world education system in Indonesia has always experienced crises, one of which is in the face of the emergency condition of the COVID-19 pandemic which has had many impacts on changes in Indonesian education. To overcome the crisis in the education system in Indonesia, the Ministry of Education and Culture (Ministry of Education, Culture, Research and Technology) is making efforts to overcome the education crisis by designing a new curriculum, namely the independent curriculum, this curriculum can be implemented in schools that are ready. The independent curriculum applies a variety of in-curricular learning to enable students to optimally develop concepts and strengthen their competencies. In this research article using the library research method, namely library research, with the technique of collecting data based on reading and writing results from several references. To achieve the goal and minimize the reoccurrence of the education system crisis, the implementation of the independent curriculum emphasizes the development of the use of technology with various available platforms and learning communities in sharing practices between teachers, students and academics, the aim is to support the success of education in Indonesia. Keyword: Education Crisis; Independent Curriculum; Educational Recovery.